Review Of Research Articles On Intrinsic And Extrinsic Motivation On Athlete Success (Journal of Physical Education Health and Sport, 2022)
Psychological skills, especially motivation, are an important component in supporting the success of athletes. Current research on motivation is still divided into two, namely intrinsic and extrinsic motivation. The two results of this study still have debates about which part has the most influence on the success of athletes reaching the golden peak in the field. Previous studies have not described each of the advantages and disadvantages of the two parts of motivation. This article aims to review the literature on the contribution of each part of motivation both intrinsic and extrinsic in supporting athlete success. The type of research carried out is to examine the results of previous studies regarding intrinsic and extrinsic motivation and then discuss each one in the qualitative category. The results or reviews in this discussion are expected to provide information that can be used as a theoretical and methodological basis for providing training or training methods in certain motivational sections to support the success of athletes, this research is considered important to be able to provide a concrete picture of the benefits of each section of motivation in athletes